Evaluation of Reinforced Concrete Structural Design of Rukost Tawakal, West Jakarta Against Earthquake Loads - Gilang Aditiya; Reynold Andika Pratama (Jurnal Teknik dan Science, 2025)
The high population density in West Jakarta has led to an increased demand for housing; however, rising property prices have become a barrier for younger generations to own a place to live. The limited land availability in densely populated areas like West Jakarta encourages the development of vertical housing as a solution to the growing residential needs, such as the Rukost Tawakal IX project. This building is designed as a five-story residence with a reinforced concrete structure. Given that Indonesia is located in an earthquake-prone region, the building’s structural system must be evaluated against seismic loads in accordance with national design standards. This study aims to evaluate the structural system of the Rukost Tawakal IX building using structural analysis software based on the provisions of SNI 1726:2019, SNI 1727:2020, and SNI 2847:2019. The evaluation focuses on the performance of primary structural elements such as columns, beams, and concrete slabs, as well as their compliance with the requirements of the Special Moment Resisting Frame (SMRF) system and the Strong Column Weak Beam (SCWB) principle, which are designated for high-ductility structures. The results of the evaluation are expected to provide recommendations for a safe, efficient, and earthquake-resistant structural design.